Immune Reconstitution After Autologous Hematopoietic Stem Cell Transplantation in Crohn’s Disease: Current Status and Future Directions. A Review on Behalf of the EBMT Autoimmune Diseases Working Party and the Autologous Stem Cell Transplantation In Refractory CD—Low Intensity Therapy Evaluation Study Investigators - Pockley, Alan Graham; Lindsay, James O.; Foulds, Gemma A.; Rutella, Sergio; Gribben, John G.; Alexander, Tobias; Snowden, John A. (Frontiers in Immunology, 2018)
Patients with treatment refractory Crohn’s disease (CD) suffer debilitating symptoms, poor quality of life, and reduced work productivity. Surgery to resect inflamed and fibrotic intestine may mandate creation of a stoma and is often declined by patients. Such patients continue to be exposed to medical therapy that is ineffective, often expensive and still associated with a burden of adverse effects. Over the last two decades, autologous haematopoietic stem cell transplantation (auto-HSCT) has emerged as a promising treatment option for patients with severe autoimmune diseases. Mechanistic studies have provided proof-of-concept that auto-HSCT can restore immunological tolerance in chronic autoimmunity via the eradication of pathological immune responses and a profound reconfiguration of the immune system. Herein, we review current experience of auto-HSCT for the treatment of CD as well as approaches that have been used to monitor immune reconstitution following auto-HSCT in patients with autoimmune diseases, including CD. We also detail immune reconstitution studies that have been integrated into the randomised controlled ASTIClite trial, which is designed to test the hypothesis that auto-HSCT using reduced intensity mobilisation and conditioning regimens will be a safe and effective means of inducing sustained control in refractory CD compared to standard of care. Immunological profiling will generate insight into the pathogenesis of the disease, restoration of responsiveness to anti-TNF therapy in patients with recurrence of endoscopic disease and immunological events that precede the onset of disease in patients that relapse after auto-HSCT.